ETIKA LINGKUNGAN DALAM FOLKLOR MASYARAKAT DESA TENGGER - Sony Sukmawan; M. Andhy Nurmansyah (LITERASI: Indonesian Journal of Humanities, 2012)
Environment ethic relies on biocentrism and ecocentrism paradigms viewing humans as an integral part of the nature assuming responsible attitutes and behaviours, good respect and care to the sustainability of living things in the universe. This kind of paradigm has actually been adopted by many adat communities in the world, including Tengger rural community. The Tenggerese ways of life and attitudes to the nature are manifestated in the varieties of folklore. The Tenggerese folklore contain forms of environmental wisdoms, such as respect, love, and care for the nature, cosmic solidarity and responsibility of the nature, no doing harm to others, and living in harmony with the nature. Keywords: environmental, wisdom, folklore, villages